2004
DOI: 10.1194/jlr.m400062-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel molecular candidates for fatty liver in the hyperlipidemic mouse model, HcB19

Abstract: The inbred HcB19 mouse strain expresses a truncated form of thioredoxin interacting protein and is phenotypically characterized by fatty liver and elevated plasma triglycerides and VLDL. Recently, these mice have been proposed as an animal model for familial combined hyperlipidemia. The aim of the present study was identification of hepatic proteins specifically associated with the presence of fatty liver. Eighteen differential proteins were detected in whole-liver homogenate from HcB19, or the parental strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In addition to these enzymes involved in methylation, the oxidoreductase glyco‐enzyme 3‐HAO was repressed in 3–month‐old rats after intrauterine exposure to alcohol. This enzyme participates in tryptophan metabolism leading to quinolate formation and NAD biosynthesis and has been suggested to be important in the development of fatty liver and hyperlipidemia 65, 66. Interestingly, we have shown that rats exposed to alcohol in utero are hyperlipidemic and develop fatty liver as adults 4.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to these enzymes involved in methylation, the oxidoreductase glyco‐enzyme 3‐HAO was repressed in 3–month‐old rats after intrauterine exposure to alcohol. This enzyme participates in tryptophan metabolism leading to quinolate formation and NAD biosynthesis and has been suggested to be important in the development of fatty liver and hyperlipidemia 65, 66. Interestingly, we have shown that rats exposed to alcohol in utero are hyperlipidemic and develop fatty liver as adults 4.…”
Section: Discussionmentioning
confidence: 68%
“…The expression level of glycerol-3-phosphate dehydrogenase increased in diet-induced obese animals [17]. Propionyl-coenzyme A-carboxylase is the key enzyme in the catabolism of odd-chain fatty acids, isoleucine, threonine, methionine and valine [18]. Phosphatidylinositol is an important lipid, both as a key membrane constituent and as a participant in essential signaling processes in all plants and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Lumiglo chemiluminescence (KPL) was used to detect bound protein, and the protein was quantified using QuantityOne® analysis software (Bio-Rad). These standard methods have been routinely used by other investigators (Chatagnon et al, 2009;van Greevenbroek, Vermeulen, & de Bruin, 2004). For the Western blot analysis of p-eNOS (ser 1177), goat polyclonal IgG obtained from Santa Cruz Biotechnology, (Santa Cruz, CA) was diluted 1:1000 for incubation overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%